Forex for Beginners A Comprehensive Guide to Profiting from the Global Currency Markets - Kritzer, Adam (Apress, 2012)
"Backed by a comprehensive list of studies, this book is a brilliant contribution on the connections between exchange rates and economics."—Francesc Riverola, CEO and Founder of FXstreet.com "Adam Kritzer has been covering the forex market for years as a prominent but accessible industry expert. In a market sector full of pitfalls for the novice, this book will help many new traders avoid costly mistakes and get started on the path to success."—Andy Hagans, Co-founder of ETF Database "Adam Kritzer is not only one of my favorite forex writers but also one of the best ... This book will likely become required reading for those getting into the forex market."—Zachary Storella, Founder of CountingPips.com Forex for Beginners: A Comprehensive Guide to Profiting from the Global Currency Markets is a guide for those who want to earn extra income trading currencies without committing large amounts of time or money. This book will introduce global investors to the basics of forex (foreign exchange) trading and provide them with a solid framework for analyzing currencies and profiting from their fluctuations. Topics covered include the forces that cause exchange rates to fluctuate, an overview of the mechanics of trading, analytical and forecasting tools, how to profit from pricing trends, and common pitfalls that often ensnare traders. While most books make grandiose promises of instant success and large profits, Forex for Beginners represents an alternative approach to investing in forex. The forex market is dominated by institutional capital and algorithmic trading, making it unrealistic to think that day traders can beat the market by relying on charts and technical indicators alone. Thus, the emphasis here is on fundamental analysis—using economic concepts to spot currency misalignments—and staking out positions to profit from them over a period of weeks and months.  If you’re eager to tap into the world’s largest financial market on a part-time basis, this is the book for you. You will gain an understanding of how currency markets work and use this knowledge to generate income.
Keywords: Business; Management science; Business and Management; Business and Management, general; Economics; Economics/Management Science; Business/Management Science, general